OLHOS QUE ESCUTAM, MÃOS QUE FALAM: Modos de subjetivação em poesias surdas - SANDRA TERESINHA DEMAMANN (2024)
Passionate about working with people with disabilities and always studying research in the area of Linguistics and Education on Deaf Literature (Karnopp, 2006, 2008); (Mourão, 2011, 2016); (Rosa, 2006, 2011, 2017), especially on deaf poetry (Quadros and Sutton-Spence, 2006); (Bosse and Karnopp, 2018), (Klamt, 2014), (Lucena, 2017), added to the need for other teaching resources that promote literary practices for deaf students in my classroom, both in the school for the deaf and in inclusion, as well as my personal interest in the cultural productions of the deaf community, I constitute the investigation of this theme for the purpose of scientific deepening and corroboration to the deaf universe. To this end, I assume that deaf poetry is part of a cultural and identity discourse, with the affirmation of deaf culture and identity. I formulate the hypothesis that these works are loaded with sayings about what it is to be deaf, as well as the struggles and barriers imposed on this community. Furthermore, these poems, by breaking with the silencing of the deaf, compose ways of existing and resisting, portray the defense and exaltation of their language, their identity and deaf culture, constitute writings of the self, as forms of self-care, self-practices, in short, they act as an exercise of the self in thought, and therefore elaborate a deaf asceticism, promoting modes of subjectivation. When looking at and feeling deaf poetry, I ask: 1. How have deaf poems, as artistic/cultural manifestations of the deaf community, been discursively constituted? 2. What enunciative regularities and dispersions materialize in these works about oneself and the other? 3. How do the words of the poems, as writings of oneself, process themselves in the subjectivation of the deaf subject? 4. What meanings emerge in the works that articulate an aesthetics of deaf existence? The general objective aims to problematize the representations and memories (through the Foucaultian notion of archive) that emerge in deaf poems as writings of oneself, constituting subjectivities of/in the production of a deaf “Aesthetics of Existence.” As specific objectives, I propose: i) To interpret the gaps, the interdictions, the silencing that expose hearing coloniality and its will to truth; ii) To discuss the effects of meaning that emerge and slip from deaf poems, understanding these enunciations as processes of subjectivation and production of a deaf “Aesthetics of Existence”; iii) Understand relations of knowledge/power and resistance permeated in the words of the poems; iv) Analyze notions such as inclusion/exclusion, normality/abnormality, difference, otherness, resistance (Foucault, 2002) and “Aesthetics of Existence”. The theoretical-methodological approach is affiliated with the transdisciplinary discursive bias at the interface with Foucaultian studies (Foucault, 2002, 2008, 2016); (Coracini, 2003, 2007); (Eckert-Hoff, 2008) and deaf studies (Skliar, 1997, 1998); (Lopes, 2007, 2011); (Karnopp, 2008, 2011). To this end, I based my work on the Foucaultian archeogenealogy methodological proposal (1996, 2008, 2011a), in which the corpus consists of (eleven) deaf poems published on YouTube. The results indicate that deaf poems are discursively constituted in a field marked by historical, political and identity tensions, articulating elements of resistance, empowerment and reconfiguration of spaces of social representation. These productions are mainly inserted in the socio-anthropological Discursive Formation (DF) of deafness and (dis)identify with the oralist DF. These creations are self-writings, in which the deaf subject (re)sews himself and (re)makes his existence (Eckert - Hoff, 2008), subjectivizing himself in/through heterogeneity and otherness. Finally, by signing or writing their poems and publishing them on YouTube, deaf people denounce and break with the prohibitions and silencing imposed on them, as well as composing other ways of existing and resisting.